Study On Capital Adequacy Of Banks In Malaysia - -, Raju Sudha (2008)
Study on capital adequacy is important not only to assess the strength of an individual bank, but also to evaluate the safety and soundness of the entire banking system in an economy. Hence, this study is undertaken with the aim to identify the factors that affect the capital adequacy of domestic and foreign commercial banks operating in Malaysia.